Neuropeptide Y-Induced Orexigenic Action Is Attenuated by the Orexin Receptor Antagonist in Bullfrog Larvae - Matsuda, Kouhei; Matsumura, Kairi; Shimizu, Syun-suke; Nakamachi, Tomoya; Konno, Norifumi (Frontiers in Neuroscience, 2017)
In bullfrog larvae at the pre- and pro-metamorphic stages, feeding behavior is regulated by appetite factors such as orexigenic peptides. In fact, food intake is enhanced by intracerebroventricular (ICV) administration of neuropeptide Y (NPY) and orexin A. Using goldfish, our previous study indicated that the orexigenic action of NPY is mediated by orexin A, suggesting the functional interaction between the two. However, there is little information about whether the action of orexin A mediates the orexigenic action of NPY in bullfrog larvae. Therefore, we examined the effect of the orexin receptor antagonist, SB334867 on the orexigenic action of NPY in larvae. The stimulatory effect of ICV injection of NPY at 10 pmol/g body weight (BW) on food intake was abolished by treatment with SB334867 at 60 pmol/g BW. These results suggest that, in bullfrog larvae, there is a neuronal relationship between the NPY and orexin systems, and that the orexigenic action of NPY is mediated by the orexin A-induced orexigenic action.